The Bible's Viewpoint and Their Creativity - Samandarova Nozima Ilhomjon qizi (Zien Journals, 2022)
This article discusses the life-styles of our country's great poets A. Avloniy and Mag'jon Jumabayev and their contributions to our literature and their books on raising the younger generation.
Keywords: Turkish Gulf or morality; pedagogy; pre-curriculum; upbringing